Do contrato de franquia: interpretação, tipicidade e convenções - Lima, Maurício Alves de (2022)
This thesis aims to review the franchise agreement in a thorough way, from its precontractual phase, through its execution phase and post-contractual phase, as a way to provide it with concrete practice and moderately perform the corresponding economic operation, known as franchising. In order to do so, legal instruments required to conclude the franchise agreement will be approached as well as main covenants to be included therein, as a way to employ accurate and complete terms to ensure stability and security in the franchise agreement execution process. The paper also addresses how foreign law has ruled this economic operation, as well as how the judiciary power of the analyzed countries have interpreted it to give a fair and balanced direction when it comes to the controversies between the contracting parties, so as to serve as a paradigm for this study. In effect, conflicts typically emerge both in business and contractual transactions when the understanding of this or that behavior or this or that contractual clause is questioned, or how to remedy any contractual gap, thus each party ends up assigning the meaning according to their own interests. Therefore, this paper aims to provide guidance towards the moderate interpretation of the franchise agreement. This understanding is based on the analysis of specific norms on the matter and the common law rules that contribute to set appropriate criteria for such purpose. The paper also reviews how the Brazilian Judiciary has construed the behaviors and the contractual covenants resulting from the economic operation known as franchising. It also reviews the precautions such judicial interference should observe to prevent the disruption of a growing economic segment that has so greatly contributed to the socio-economic development in Brazil